1985
DOI: 10.1002/pssa.2210870220
|View full text |Cite
|
Sign up to set email alerts
|

The superposition of thermal activation in dislocation movement

Abstract: The thermally activated movement of a dislocation intersecting a small density of strong point obstacles imbedded in a large density of weak obstacles is calculated analytically by modelling the geometrical correlations. The superposition of the flow stresses for the isolated processes is only valid for zero temperature. At high temperatures only the strong obstacles impede the movement wheras at low temperatures the weak obstacles contribute to or controll the flow stress. It is suggested that the plateau‐str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In general, it turns out that the dislocation motion may indeed be characterized by an Arrhenius-type rate equation, but the activation enthalpy is a complicated function of stress, temperature and obstacle density and strength. The problem was approached analytically by Landau and Dotsenko [8] and Schlipf [9] for systems with random identical obstacles and by Arsenault and Cadman [10], Zaitsev and Nadgornyi [11] and Schoeck [12] for distributions of obstacles with two different strengths and activation enthalpies. These studies used various simplifying assumptions of which the most important is disregarding spatial correlations between obstacle failure events along given dislocation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it turns out that the dislocation motion may indeed be characterized by an Arrhenius-type rate equation, but the activation enthalpy is a complicated function of stress, temperature and obstacle density and strength. The problem was approached analytically by Landau and Dotsenko [8] and Schlipf [9] for systems with random identical obstacles and by Arsenault and Cadman [10], Zaitsev and Nadgornyi [11] and Schoeck [12] for distributions of obstacles with two different strengths and activation enthalpies. These studies used various simplifying assumptions of which the most important is disregarding spatial correlations between obstacle failure events along given dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…The approach of Schoeck [12] is aimed at relaxing this limitation, but it eventually leads only to asymptotic predictions. Several computer simulations of thermally activated dislocation motion were also performed [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The simulations (figure 8) suggest that the backstress σ b is effectively a lower bound on the strength at finite temperature; when σ < σ b , the forest would contribute an activation energy G 0 f which is far larger than can be achieved through thermal activation. Resolution of this issue is achieved in part by considering the contributions to the strain rate from dislocation motion through the solutes in regions between the low density of forests, along with the lines of Schoeck [32], leading to an overall strain rate ε = ρ m bν 0 1 √ ρ f exp G k B T + √ ρ s exp G s k B T (23) where ρ m is the mobile dislocation density, G is the overall activation energy computed from equation (15), ρ s is the solute density and G s is the activation barrier associated with soluteonly field. However, when G is large, even at very small ρ f and low σf , the thermal activation energy is dominated by the forest.…”
Section: Discussionmentioning
confidence: 99%
“…σ α (ε, T ) = σ α 1 (ε, T ) + σ α 2 (ε, T ), but without fundamental justification [25,30,31]. Schoeck [32] theoretically studied the thermally activated motion of a dislocation line in a field containing a low density of obstacles with high activation energy and a high density of obstacles having low activation energy. He concluded that the linear additivity at finite temperature did not follow from linear additivity at T = 0.…”
Section: Introductionmentioning
confidence: 99%